Pharmacovigilance Study on Safety Assessment of Nicorandil - Pathak, Vishwas; Sharma, Rajesh (Journal of Neonatal Surgery, 2025)
Background: The chronic use of the antihypertensive drugs make patients more vulnerable to experience adverse effects that are either known to occur (expected adverse drug reactions) or are not known to occur (unexpected adverse drug reaction, previously unknown adverse reaction). Pharmacovigilance is the science and activites related to the continuous assessment of benefit risk profile of the drug to understand the safety profile of the drug for continuous use. Aim and Objective: Pharmacovigilance study was conducted to study the safety profile of Nicorandil in patients of hypertension. Study Design: Non-interventional, observational, cohort study. Materials and Methods: The study was conducted using active drug surveillance methodology of pharmacovigilance. The valid individual case safety reports were identified from the Pub Med database using international nonproprietary name <Nicorandil>. The coding of event terms was done using medical dictionary for drug regulatory activity. WHO-UMC causality assessment scale was used for performing cause and effect analysis. Results and Discussion: A total of 18 valid case reports with 19 adverse drug reactions were identified (males=09; females=08; missing demographic detail = 01). Maximum patients (n=12) were in the age group of 70-80+ years and least number of patients were in the age group of 40-50 years. Comparison of reported ADR(s) was done with EMEA Summary of Product Characteristics of Nicorandil. The ADR ‘Cyanosis’ was not reported in the EMEA SmPC , however the same was reported in our study. Occular side effects were identified as signals from the study. Conclusion: All reported ADR(s) are expected except the ADR of ‘Cyanosis’. The expected ADRs are well known to occur with formulations containing Nicorandil.